Comparative Effectiveness of Rheumatic Exercise Therapy and Progressive Muscle Relaxation on Joint Pain among Older Adults with Osteoarthritis - Adhin Al Kasanah; Edy Purwanto; Binar Wahyuning Widhi (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Osteoarthritis is one of the most common degenerative diseases among older adults and often causes joint pain, leading to decreased mobility and quality of life. Various non-pharmacological interventions have been implemented to reduce joint pain, including Progressive Muscle Relaxation (PMR) and rheumatic exercise. However, studies comparing the effectiveness of these two interventions remain limited. Objective : to determine the difference in effectiveness between Progressive Muscle Relaxation and rheumatic exercise on joint pain among older adults with osteoarthritis. Methods: This study employed a quasi-experimental design with a pretest-posttest two-group approach. A total of 34 older adults with osteoarthritis were recruited and divided into two groups: Progressive Muscle Relaxation group (n=17) and the rheumatic exercise group (n=17). Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using the Shapiro-Wilk test, Wilcoxon Signed Rank Test, and Mann-Whitney Test with a significance level of α=0.05. Results: The mean pain score in the Progressive Muscle Relaxation group decreased from 5.71±1.21 to 3.82±1.24 (p=0.00008). In the rheumatic exercise group, the mean pain score decreased from 4.18±1.13 to 2.12±0.93 (p=0.00016). The Mann-Whitney test revealed no significant difference in effectiveness between Progressive Muscle Relaxation and rheumatic exercise in reducing joint pain among older adults with osteoarthritis (p=0.283). Conclusion: Both Progressive Muscle Relaxation and rheumatic exercise are effective in reducing joint pain among older adults with osteoarthritis. However, no significant difference in effectiveness was found between the two interventions